Plant Height, Number Of Leaves, And Flowers Of Tomato (Solanum lycopersicum L) After The Application Of Eco-Enzyme From Nutmeg Leaf Waste - Muhammad Rijal; Sulastri Sulastri; Laila Sahubauwa; Dian Safitri; Salma Samputri; Adriana Hiariej; La Ridwan (UNIVERSITAS KHAIRUN, 2025)
Eco-enzyme is a liquid fertilizer resulting from the fermentation of organic waste such as fruit and vegetable pulp, sugar and water in the manufacturing process which is quite long, around 3 months. The eco-enzyme solution is dark brown and has a strong sweet and sour fermentation aroma. Eco-enzyme contain various types of enzymes such as protease, lipase, and amylase which are very beneficial for plants and contain many microorganisms. This type of research is quantitative with a field experiment approach, which was carried out on August 19-November 27, 2024 which is located next to the IAIN Ambon Student Center building. The object of this research is tomato fruit plants that are given different concentrations of eco-enzyme. The research design used is a randomized block design consisting of 5 treatments and 4 groups so that the number of observation units is 20 units. The results showed that the provision of eco-enzyme with different concentrations (100%, 80%, 60%, 40%, 20%) was significant to the increase in plant height, number of leaves and number of flowers. In the provision of eco-enzyme concentration of 20%, the average increase in plant height was 53.25 cm, the average increase in the number of leaves was 13 strands, the average increase in the number of flowers was 3.25 buds. The difference test for each treatment using HSD-Tukey showed that the treatment of eco-enzyme concentration 20% (K5) was better than the other treatments.